Synthesis of aluminium pillared clay and their adsorption capacity for Cd2+ removal from water - Duc, Truong Dinh; Bang, Nguyen Van (Vietnam Journal of Chemistry, 2012)
Di Linh clay was used for pillaring in the present study after refinering. Aluminum pillared clay (Al-PILC) was prepared by contacting of aluminum pillaring agent and Na-montmorillonite (MONT-Na) aqueous suspension with different ratios. The obtained materials were characterized by XRD, IR, DTA-TGA, SEM, BET and 27Al-MAS-NMR methods. The increase in d001 of basal spacing was as expected since the pillaring causes an expansion in the interlayer distance. SEM method is used to probe the change in morphological features of MONT-Na and Al-PILC. The surface morphology of MONT-Na is different from that of Al-PILC. The MONT-Na appears as corn flake like crystals, revealing its extremely fine platy structure. After pillaring, clay has become more porous. This porous appearance probably occurs due to the pillars formed between the interfaces of clay sheets as a result of pillaring and the reduction in certain amorphous phase originally associated with the MONT-Na. Removal of Cd2+ from aqueous solution by adsorption using Al-PICLs was investigated at different pH values. The experiment results showed that 7.5 Al-PICL is the best choice for removal of Cd2+ from water before re-use.